Sublethal levels of organophosphate insecticides alter behaviour in the juveniles of the Neotropical crab, Poppiana dentata (Randall 1840). Issue 2 (4th March 2023) - Singh, Delezia S.; Rostant, Luke V.; Mohammed, Azad; Jairam, Alyssa S.; Sahatoo, Jyotsna J.; Khan Ali, Raquel; Mohammed, Faisal
HIGHLIGHTS: This is the first description of OP-induced behavioural alterations for juvenile P. dentata Aggression and inactivity were induced by the OPs The insecticides reduced feeding (e.g. eating) in exposed crabs Impacts were also associated with vulnerability and hampered survivorship Behavioural alterations induced by xenobiotics, like pesticides, have not been assessed for many Neotropical crab species. This study sought to evaluate such effects on juvenile Poppiana dentata, exposed to two organophosphate (OP) pesticides under laboratory conditions. Treatments involved a control, solvent control (xylene), malathion and diazinon commercial insecticides, with the OPs administered in three logarithmically increasing concentrations of 0.1, 1 and 10 µg/L. A pre-established ethogram was used to document behavioural acts for treatments; foraging, eating, grooming, locomotion, quiescence (inactive), prolonged agonism, non-agonistic contact and moulting. Each treatment cohort was continuously recorded over a 72 hr period. The time durations for each act were determined from the video footage (n = 2, 304 hr) and used to determine time spent on each behavioural act, over a 24 hr time period. Time spent by OP-exposed crabs on each act differed significantly from those of the controls. Diazinon-exposed crabs spent most of their daily time in heightened agonistic behaviour (43.4–71.6%). Malathion-exposed crabs spent the majority of their time being inactive (46.7–79.0%) and xylene-exposed crabs exhibited similar behavioural alterations of heightened aggression (53.6%) and inactivity (39.3%). OP-induced changes in essential behaviours of juvenile P. dentata can increase vulnerability, hamper survival and increase risk to predators via impaired locomotion, induced inactivity and limited energy availability, through reduced food intake. These findings provide a better understanding of OP-induced behavioural alterations in juvenile P. dentata and the long-term consequences for essential processes like growth, reproduction and survival.